ANALISIS KARAKTERISTIK KAPASITAS MASYARAKAT DALAM PENGELOLAAN HUTAN LINDUNG GUNUNG GEULIS KABUPATEN SUMEDANG JAWA BARAT-INDONESIA - Pujo, Pujo (Wanamukti: Jurnal Penelitian Kehutanan, 2024)
Community-based forest management or social forestry approach has been implemented to increase community involvement in forestry development. Community capacity to collaborate is needed to realize sustainable community-based forest management. The object of research is to determine the community capacity characteristics and the factors that influence community capacity in developing forest management cooperation. The method of research by survey methods with purposive sampling was 60 respondents. The community capacity characteristics were analyzed using the factor analysis method. The research results found that the community capacity characteristics can be grouped into 2 (two), namely: individual level and group or community level. The individual level is described by 16 variables. The new knowledge about the level of grouping which describes the existence of levels or ladders of community capacity characteristics starting from the lowest variable is sense of community to the highest variable, namely social capital. The results of statistical tests on the community capacity characteristics show that the level of community capacity in collaborating is low category. The results of this research confirm one of the community capacity characteristic variables that has a strong influence namely social capital. Therefore, cooperative behavior in managing MGPF needs to be increased by developing community capacity through strengthening social capital.   Keywords: community capacity, cooperation, community-based forest management.